Transformation of Ulayat Land Administration: Collaborative Governance Perspective in West Sumatra - Puri, Wulan Puspita; Puspa Dewi, Ni Luh Gede Maytha; Kartika, Widya (Universitas Teuku Umar, 2024)
Customary land administration in West Sumatra has been carried out for a long time. However, many issues have arisen due to the administration of communal land needing to recognise communal rights to land ownership optimally. As mandated in the Basic Agrarian Law, the government is carrying out an administration transformation carried out by the Ministry of ATR/BPN starting in 2021, the customary land administration scheme is carried out with the customary land protection scheme which is granted through the granting of Land Management Rights (HPL) to customary authorities. The transformation of customary land administration is carried out with a Collaborative Governance perspective to optimize the program’s success. This study uses descriptive research methods through a qualitative approach with literature studies to analyze the transformation of customary land administration in the concept of collaborative governance in West Sumatra. Research results show that collaboration and partnership in the administration of communal land have represented essential elements in the principle of Collaborative Governance. Research also shows the failure to achieve consensus on the coordination and collaboration process, so the Pilot Project, which was planned in 3 districts, was successfully implemented in 2 districts, namely Tanah Datar District and Lima Puluh Kota District.